Power of a meromorphic function that share a set with its derivative - CHAKRABORTY, Bikash (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this article, we deal with the problem of the uniqueness of the power of a meromorphic function with its derivative counterpart sharing a set and thus improve our recent result under some constraints. Mathematics Subject Classification (2010): 30D35.